Penerapan Total Quality Management Pada Dunia Pendidikan Dalam Meningkatkan Kinerja Tenaga Kependidikan - Indra Gunawan; Maman Hariana; Omanudin Omanudin; Tri Ngudi Wiyatno (Departement of Mathematics Education, 2024)
This research aims to analyze the application of Total Quality Management (TQM) in improving the performance of education staff. In an era of globalization that demands improving the quality of education, TQM is considered a strategic approach that is able to increase the efficiency and effectiveness of education personnel. The research method used is a case study with a qualitative approach. Data collection was carried out through direct observation, in-depth interviews with school principals, teachers and administrative staff, as well as analysis of documents related to the implementation of TQM in selected vocational schools. The research results show that the implementation of TQM contributes significantly to improving the performance of education personnel in several main aspects: first, through strengthening a quality culture that emphasizes the importance of student satisfaction and achieving high education standards; second, continuous work process improvement through the Plan-Do-Check-Act (PDCA) cycle; and third, increasing job satisfaction and professionalism of educational staff through continuous training and career development programs. In addition, key factors that support the successful implementation of TQM in the educational environment include strong commitment from school management, active involvement of all stakeholders, and effective and transparent communication. This research also identifies challenges in implementing TQM, such as resistance to change and limited resources, but emphasizes that the long-term benefits of implementing TQM are much greater. The conclusion of this research is that TQM is an effective and efficient strategy in improving the performance of educational staff in vocational schools, and therefore, can be adopted more widely by other educational institutions. Successful implementation of TQM will have a positive impact on the overall quality of education, so that it can produce graduates who are competent and ready to compete in the world of work.